Original articleTranscatheter closure of persistent ductus arteriosus in adult patients – our experience - Szkutnik, Małgorzata; Kusa, Jacek; Banaszak, Beata; Obersztyn, Anna; Regiec, Stanisław; Łapa, Piotr; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2007)
Introduction: Patent ductus arteriosus (PDA) in adult patients has a different structure than in children, which may cause difficulties and complications during surgical closure. Methods: In our centre from a group of 403 patients (pts) with PDA closed percutaneously, 75 adult pts aged 16-84 (mean 32) were separated for the study. We applied according to implant availability and the duct anatomy (diameter and type) the following devices: Starflex (SF) and double Rashkind umbrella (R), detachable coils (C) or Amplatzer Duct Occluders (ADO). Results: ADO were used in 39 patients, coils in 25 patients (simultaneously 2 coils in 3 patients), R in 7 patients, and SF in 4 patients. We observed device embolization to the pulmonary artery (PA) in 2 patients from group C. In 2 other patients in group C the coil position was unstable so both implants were withdrawned. Residual leak was observed in 2 other patients in whom primary C were used and in 1 patient in whom R was applied. In all these patients residual leak was successfully closed using another C. A good result was achieved in patients with “window” type PDA treated by SF umbrella. Conclusions: Transcatheter PDA closures is an effective and safe procedure in adult patients. In the case of conical and tubular PDA of medium to large size the best results were obtained when ADO was used. Double Starflex umbrella is optimal for “window” type PDA closure, whereas detachable coils show high efficacy for closing small PDA and residual leaks after previous transcatheter or surgical procedures.